Global Employment and Social Developments. Issue 1 (27th April 2017) - Andrianov, Vladimir; Bourmpoula, Valia; Chacaltana, Juan; Dasgupta, Sukti; Duda, Marta; Ernst, Ekkehard; Haidar, Salwa; Horne, Richard; Huynh, Phu; Jafaar, Aya; Khatiwada, Sameer; Kim, Kee Beom; et al.
Abstract : The chapter gives a global overview of recent labour market developments and short‐ and medium‐term projections for employment and wages. The chapter discusses recent changes in occupational employment and how they affect inequality and wages. The chapter also highlights the importance of rising youth unemployment for social unrest across major world regions.